Heat and moisture transfer behaviour in Phyllostachys edulis (Moso bamboo) based panels. (30th March 2018) - Huang, Puxi; Chew, Y.M. John; Chang, Wen-Shao; Ansell, Martin P.; Lawrence, Mike; Latif, Eshrar; Shea, Andy; Ormondroyd, Graham; Du, Hu
Highlights: Coupled heat and moisture transfer experiments and simulations of Moso bamboo panels were conducted. A series of parametric studies of numerical simulation are firstly presented in this paper. Different lamination methods were implemented on Moso bamboo specimens. Abstract: This study focuses on the heat and moisture transfer behaviours in the Phyllostachys edulis (Moso bamboo) panels at various temperature and relative humidity (RH) conditions. Moso bamboo panels with different lamination methods were prepared by assembling bamboo strips from different layers of the bamboo culm wall. Dynamic coupled heat and moisture transfer experiments were conducted. Unsteady state numerical modelling was conducted by COMSOL Multiphysics™. A rigorous approach was adopted in this paper. A series of parametric studies of numerical simulation are firstly presented in this paper and then validated by the experiments. Both experimental and simulation results appear to be consistent with the results of measurements of the basic hygrothermal parameters, which demonstrates the robustness of the results. The temperature and RH results indicated that although the panel made from layers of the internal part of bamboo culm wall can provide good insulation performance, its ability to resist high RH variation is inferior to the layer from the external part of bamboo culm wall. The parametric study found that density is the most critical parameters to influence the temperature distributions in the transient state. The thermal conductivity dominates the temperature variation in the steady state. The water vapour diffusion resistance factor is the key parameter which influences the RH simulation results. Numerical simulation with moisture transfer shows better consistency than the simulation without moisture in both equilibrium and transient states. The results of this study demonstrated that the external part of the bamboo culm wall can be utilised to minimise the RH variation of the panel while the internal part is suitable for increasing the thermal insulation performance of the panel.